Genetic characterization of B-cell prolymphocytic leukemia: a prognostic model involving MYC and TP53 - Chapiro, Elise; Wagner, Lena; Scheinost, Sebastian (Blood, 2019)
This article presents a comprehensive genetic, clinical, and drug sensitivity analysis of a large series of B-prolymphocytic leukemia cases, illustrating new fi